Convergence and Reciprocity in Cross Regional Santri Communication: Konvergensi dan Timbal Balik dalam Komunikasi Santri Lintas Wilayah - rama adi wijaya; Kukuh Sinduwiatmo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Islamic boarding schools in Indonesia serve as religious educational institutions and social environments where students from diverse cultural and linguistic backgrounds interact. Specific Background: At Faqih Hasyim Islamic Boarding School, cross-regional santri encounter language differences and cultural diversity that shape their interpersonal interaction patterns. Knowledge Gap: Limited research explains how communication adaptation occurs among santri from different regions within multicultural pesantren settings. Aims: This study investigates communication adaptation processes among cross-regional santri using Interaction Adaptation Theory. Results: Using a qualitative descriptive approach through observation and in-depth interviews, the study identifies two dominant adaptation patterns, namely convergence mirroring, where students adjust linguistic style and behavior to resemble peers, and reciprocity compensation, where students maintain interaction balance through partial adjustment and flexibility. The findings also reveal the absence of divergence patterns, reflecting the pesantren cultural emphasis on harmony and social unity. Novelty: This study provides empirical evidence of interaction adaptation dynamics within a multicultural Islamic boarding school context using Interaction Adaptation Theory as an analytical framework. Implications: The findings indicate that adaptive communicative competencies support the development of empathy, tolerance, and cohesive social relationships within diverse pesantren communities, contributing to intercultural communication discourse in Islamic educational institutions. Highlights: Two Interaction Adjustment Mechanisms Dominate Interpersonal Exchanges Among Students From Different Provinces. Harmony-Oriented Institutional Culture Discourages Contrasting Behavioral Responses During Social Interaction. Flexible Linguistic and Behavioral Alignment Supports Empathetic and Tolerant Relationships Within Diverse Learning Environmen Keywords: Interaction Adaptation Theory, Islamic Boarding Schools, Intercultural Communication, Language Differences, Multicultural Students